Wildlife Value Orientations towards Hunting among Communities in Bintulu, Sarawak: A Comparison of the Demographic Factors - Thomas, Alexander; Lin, Evelyn Lim Ai; Johari, Shazali Bin; Mariapan, Manohar (Jurnal Manajemen Hutan Tropika, 2025)
Communities living near forest areas have long hunted wildlife for food and other products. Among the communities in Bintulu, Sarawak, traditional hunting and the consumption of wildlife meat are deeply ingrained in their culture. This study identifies the wildlife value orientation among communities in Bintulu, Sarawak, and compares their values with demographic factors, including gender, residency, age, and education level. A survey was developed to identify the communities' value orientation towards hunting, specifically the utilitarian, cultural/traditional, and conservation values. A total of 413 residents were surveyed, including individuals with knowledge of hunting practices and those who consume wildlife products, even if not active hunters themselves. Findings revealed that communities in Bintulu hold multiple values towards wildlife hunting, with a stronger tendency towards conservation values. When the demographic factors were compared, males exhibited stronger utilitarian and cultural/traditional values. Rural residents displayed higher utilitarian and cultural/traditional values, yet they also had stronger conservation values. Communities aged 40 and above displayed higher utilitarian, cultural/traditional, and conservation values. Those with lower levels of education, including primary and no formal education, show stronger conservation values than those with tertiary education. These findings emphasize the diversity of perspectives toward wildlife use and highlight the need for conservation strategies that align with local cultural contexts. Balancing traditional practices with ecological sustainability offers a more inclusive and region-specific approach to wildlife management and conservation policy.